The Elements of the Very Short Story in Ahmad Matar’s Lafa’at - Fattah, Ali (Al-Adab Journal, 2023)
This research deals with approaching the texts of the poet (Ahmed) Matar, and reading them from a narrative angle, using the pillars of the very short story to reach the desired goal, due to the great similarity between these creative texts and the very short story, because it includes the most important pillars of the very short story, starting from the narrative. Passing through condensation, unity, and ending with paradox, in addition to the secondary elements of humanization of animals, astonishment, and the frequent use of phrasal verbs. It contains the most important elements of the artistic story, such as narration, description, characters, events, time, place, dialogue, and a narrative perspective. The narrative is one of the most important dominant elements of Ahmed Matar’s texts, similar to the very short story, as without it its narrative structures are disturbed, and the narrative is defined in four overlapping elements (event, personality, time and place). The nature of Matar’s poems imposes brevity and condensation on him, due to the limited space in front of him, as he is doomed to communicate his idea through words or lines, so condensation includes event and narration, description, subject, idea, and environment, so he dissolves the various elements and components into each one or a single focus that shines like lightning. Most of his texts are based on narrative condensation and brevity in detailing the narrative plot, focusing on a brief introductory, and presenting the knot in a focused manner by preserving the unity that is an important pillar on which the very short story is based. The fatality of the story, especially if it is marred by a kind of contradiction, provided that this unity does not lead to ambiguity and weakness in the delivery, but is based on the language of evasion, and bringing what the reader does not expect through the paradox that surprises and surprises him through contradiction.